Evaluation of Army Engine Oils in Hydraulic/Power Transmission System Components. - Marbach,H W , Jr; Lestz,S J (1985)
The objective of the MACI Hydraulic System and Components Program is to perform technical evaluation and assessment of commerically available qualified and fielded Army engine oils and to determine if such oils can be used as hydraulic fluids in Army commercial construction equipment and material handling equipment. Five Army specification engine lubricants--four MIL-L-2104D (one grade 10W, one grade 30, two grade 15W-40) and one MIL-L-46167, grade 0W-20--were evaluated using four critical component performance tests used by manufacturers. Data compiled from this and previous work have shown that the limiting factors of the Army engine oils used as hydraulic and multipurpose power transmission fluids appear to be (1) wet-brake chatter noise, (2) hydraulic pump wear problems with some piston pumps using MIL-L-46167 Arctic engine oils at temperatures hotter than expected Arctic conditions, and possibly (3) copper corrosion. The prime area of concern is the wet-brake chatter noise. (Author)